Overexpression of chloroplast NADPH-dependent thioredoxin reductase in Arabidopsis enhances leaf growth and elucidates in vivo function of reductase and thioredoxin domains - Toivola, Jouni; Nikkanen, Lauri; Dahlström, Käthe M.; Salminen, Tiina A.; Lepistö, Anna; Vignols, Florence; Rintamäki, Eevi (Frontiers in Plant Science, 2013)
Plant chloroplasts have versatile thioredoxin systems including two thioredoxin reductases and multiple types of thioredoxins. Plastid-localized NADPH-dependent thioredoxin reductase (NTRC) contains both reductase (NTRd) and thioredoxin (TRXd) domains in a single polypeptide and forms homodimers. To study the action of NTRC and NTRC domains in vivo, we have complemented the ntrc knockout line of Arabidopsis with the wild type and full-length NTRC genes, in which 2-Cys motifs either in NTRd, or in TRXd were inactivated. The ntrc line was also transformed either with the truncated NTRd or TRXd alone. Overexpression of wild-type NTRC promoted plant growth by increasing leaf size and biomass yield of the rosettes. Complementation of the ntrc line with the full-length NTRC gene containing an active reductase but an inactive thioredoxin domain, or vice versa, recovered wild-type chloroplast phenotype and, partly, rosette biomass production, indicating that the NTRC domains are capable of interacting with other chloroplast thioredoxin systems. Overexpression of truncated NTRd or TRXd in ntrc background did not restore wild-type phenotype. Modelling of the 3-dimensional structure of the NTRC dimer indicates extensive interactions between the NTR domains and the TRX domains further stabilize the dimeric structure. The long linker region between the NTRd and TRXd, however, allows flexibility for the position of the TRXd in the dimer. Supplementation of the TRXd in the NTRC homodimer model by free chloroplast thioredoxins indicated that TRXf is the most likely partner to interact with NTRC. We propose that overexpression of NTRC promotes plant biomass yield both directly by stimulation of chloroplast biosynthetic and protected pathways controlled by NTRC and indirectly via free chloroplast thioredoxins. Our data indicate that overexpression of chloroplast thiol redox-regulator has a potential to increase biofuel yield in plant and algal species suitable for sustainable bioener